Pengaruh Current Ratio dan Inventory Turnover terhadap Return on Asset pada Perusahaan Sub Sektor Semen - Muhammad Fikry Rivaldy; Leni Nur Pratiwi; Banter Laksana (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This research aims to analyze the effect of Current Ratio and Inventory Turnover on cement sub-sector companies listed on the Indonesia Stock Exchange (BEI) for the period 2012-2019. This research uses a purposive sampling method and obtains a sample of 4 companies. The analysis used to determine the effect of Current Ratio and Inventory Turnover is statistical analysis with the help of Eviews 10 software. Testing is done by linear regression of panel data with independent variables used, namely Current Ratio (CR) and Inventory Turnover (ITO). The results showed that the Current Ratio had no partial effect on Return On Assets and Inventory Turnover had no partial effect on Return On Assets. Current Ratio and Inventory Turnover have a simultaneous effect on Return On Assets.